Analysis of Sharia Economic Law on Childcare Service Transactions: Wadiah, Ijarah, and Child Protection - Misi Anggraini (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2025)
This research examined the conformity of child custody transactions with the concept of wadi???ah in Islamic economic law. The demand for child custody increased, but wadi???ah required deposits in the form of goods, not living beings who possessed rights and dignity like children. A normative juridical method was used to analyze the principles of classical Islamic law and modern child custody practices involving contracts, fees, and security guarantees. The study???s results showed that children could not be treated as objects of deposit in wadi???ah because they had fundamental rights. Therefore, child custody transactions were more appropriately studied through other sharia contracts such as ijarah (service leasing) or wakalah (representation). This research highlighted the ethical and legal dilemmas implicitly related to the commodification of children in current practices. It also emphasized the importance of a legal framework that safeguarded the rights and dignity of children while providing protection for parents, as well as accommodating the social needs of child care services according to sharia principles. These findings enriched the discourse between social needs and Islamic economic ethics.